Los pretorianos en Washington - Palomo Garrido, Aleksandro (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
The Army and the industrial armament concern have been reaching a greater leading role in the american society, wich it has been realizing as a greater politic power. With Bush´s presidential election, we could talk about the rise to the power of a verified court formed by pretorians